Analisis Kinerja Bisnis Jasa Carbon Dan Painting Carbon Plus Di Kota Palembang - Sumantri, Stephen; Kasih, Yulizar (Universitas Multi Data Palembang, 2024)
Carbon Plus is an automotive business specializing in Carbon Kevlar products, which are made from carbon kevlar fibers and can be used as coatings for vehicle parts, both for cars and motorcycles, as well as other components. The business offers three services: carbon skinning, carbon repairing, and painting. Located at Sakura I Street, Palembang, Carbon Plus plans to promote its services through Instagram and ads on social media.. The performance analysis of the Carbon Kevlar business is conducted by considering financial, operational, market, risk, innovation, and sustainability aspects to evaluate the efficiency, profitability, and social and environmental impact of Carbon Kevlar production and marketing activities. The main focus is on increasing revenue, production efficiency, market dominance, risk management, product innovation, and corporate social responsibility.